The Influence of Motifations and Job Abilities on Employee Performance - Maftukah, Laela; Kristiana, Ari (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Employee performance is any effort made to improve company or organizational performance, which includes the performance of each employee and work unit within the company. Salary increases and bonuses are factors that greatly motivate employee performance improvement. The degree of education that is part of work abilities can boost employee performance. The goal of this study was to ascertain if the capacity and motivation to work simultaneously had a major impact on the performance of employees at the Kapasan Fish firm in Kecipir Village, Losari District.  is significantly impacted by both talent and work motivation at the same time. 36 respondents who participated in the study served as samples. Utilized are primary data categories, which are gathered through observation, interviews, and the distribution of questionnaires. SPSS is used in this work for data processing and analysis, including determination analysis and multiple linear regression analysis. For assessing hypotheses, the t test and f test are employed. With a t-value of 1.682 t tabel of 1,692 and a significance value of 0.085, the analysis's findings demonstrate that employee performance is not substantially impacted by job motivation. Work ability has a considerable impact on employee performance, as shown by the t value of 1.773 t table of 1.692 and a significance value of 0.000. The f count 18.789 f table 4.14 and significance value of 0.000 show that both work motivation and work ability have a substantial impact on employee performance.